EXAMPLE OF DIVIDING LIFE CYCLE MODEL OF INDUSTRIAL CLUSTERS ON STAGES - O. G. Kazeeva (Вестник университета)
The results of a research of the stages of the life cycle of an industrial cluster and the factors that determine these stages have been presented. Examples and criteria for distinguishing a different number of stages of the cluster life cycle, various goals pursued by different authors dividing the cluster life cycle in stages have been provided. Descriptions of the criteria of the stages of the life cycle have been given , the choice of these criteria has been substantiated, and also the purpose of studying the life cycle of the cluster with the subsequent division of it into stages has been determined. The concepts of “heterogeneity” and “profile of intracluster interactions” have been introduced and their definitions have been given. Eight characteristics of interactions for constructing a general indicator of the interactions profile have been described.